Effects of Temperature, Scarification, Stratification, Phytohormones, and After-Ripening on the Dormancy and Germination of Eucommia ulmoides Oliv. Seeds - Shiming Deng (MDPI AG, 2021)
Eucommia ulmoides Oliv., the only member of the family Eucommiaceae, is endemic to China and has great development and utilization prospects. The seeds of E. ulmoides show dormancy but the underlying mechanism remains unknown. The aim of this study was to determine the cause of the seed dormancy and provide fundamental knowledge for the breeding, genetic improvement, and conservation of the germplasm resources of this species. According to the seed dormancy classification system developed by Jerry M. Baskin and Carol C. Baskin, we compared the germination percentage between intact seeds and isolated embryos, constructed water absorption curves, and evaluated the germination of seeds treated with scarification, cold/warm-moist stratification, after-ripening during dry storage, and gibberellic acid (GA3). The results showed that the intact seeds germinated only at 10 °C with a low germination percentage of 13.3% whereas the isolated embryos had a high normal germination percentage among a wider range of temperatures. According to the results from the scarified seeds, half seeds, and intact seeds, the seed coat significantly restricted the embryo water absorption. The scarification, after-ripening, cold/warm-moist stratification, and GA3 treatments promoted seed germination. Among them, cold-moist stratification was the most effective method and the temperature range of seed germination increased in both directions from 10 °C with prolonged stratification. The germination percentage increased significantly at constant temperatures with the highest germination percentage of 93.7 ± 0.3% at 10 °C and a light/dark cycle after 90 days of cold-moist stratification. Therefore, the freshly harvested E. ulmoides seeds exhibited a combinational dormancy comprising physical and Type 3 non-deep physiological dormancy, causing limited embryo water absorption by the seed coat and a low embryo growth potential. Given the unique phylogenetic characteristics and utility of E. ulmoides, our findings should promote studies of seed dormancy evolution and the development and application of E. ulmoides germplasm resources.